The experience of disease in cystic fibrosis: the paths to comprehensive care - Pizzignacco, Tainá Pelucio; Mello, Débora Falleiros; Lima, Regina Garcia (Revista da Escola de Enfermagem da USP, 2011)
Cystic Fibrosis is a chronic disease with an extensive impact on family life. The experience of disease is the manner how individuals respond to the disease, assigning meaning meanings and searching for ways to deal with it in their daily lives. The objective of this study was to understand the experience of Cystic Fibrosis in the family context. This is an ethnographic study, performed with families of children assisted at a teaching hospital located in the state of São Paulo. Results were divided into the themes past, present and future, and all phases were permeated with the search for the meaning of the disease and social support, the importance of religion and spirituality, and child's socialization. Knowing the experience in the disease and the social network is indispensible when planning comprehensive care. This is an innovative approach in health care for chronic diseases.